Abnormalities of CD4 T cell subpopulations in ANCA-associated vasculitis - Marinaki, Smaragdi; Neumann, Irmgard; Kälsch, Anna-Isabelle; Grimminger, Peter; Breedijk, Annette; Birck, Rainer; Schmitt, Wilhelm; Waldherr, Rüdiger; Yard, Benito A.; Woude, Fokko J. van der (Clinical & experimental immunology, 2005)
In patients with ANCA-associated vasculitis (AAV), CD25 expression is increased on circulating T cells. Although in animal experiments the role of CD4(+) CD25(+) T-regulatory-cells (T(reg)) in protection against autoimmunity is well established, the role of these cells in AAV is unknown. To investigate the hypothesis that an increased expression of CD25 on T cells is related to persistent T cell activation and not to disturbances in T(reg) cells in AAV (34 patients, six of them after renal transplantation), we investigated CD25 expression in different subpopulations of CD4(+) cells and FOXP3 mRNA expression by reverse transcription-polymerase chain reaction (RT-PCR). In addition, T cell proliferation and cytokine secretion after stimulation with anti-CD3 and anti-CD28 and intracellular cytokine production after stimulation with phorbol myristate acetate (PMA)-ionomycin was determined. Controls were non-vasculitic renal transplant patients (n = 9) and healthy controls (HC) (n = 13). In AAV the total number of lymphocytes, CD4(+) lymphocytes and the percentage of naive T cells are lower than in HC and RTX. An increased percentage of CD25(+) cells was found in AAV and AAV/RTX, irrespective of disease activity, but not in HC or RTX. This was confined to the naive (CD4(+) CD45RB(high)) population only. FOXP3 mRNA expression in CD4(+) T cells did not differ between AAV patients and healthy controls. In vitro T cell proliferation was enhanced in AAV patients compared to HC (P < 0.01). PBMC of AAV patients produced significantly less interleukin (IL)-10 and interferon (IFN)-gamma after anti-CD3/CD28 stimulation. The percentage of IL-10 and IL-12, but not IFN-gamma, IL-4 or tumour necrosis factor (TNF)-alpha-producing cells was significantly higher in patients compared to HC. These findings were confined to the memory population of CD4(+) cells. We conclude that AAV patients are lymphopenic and have low numbers of CD4(+) T cells, which seem to be in a persistent state of activation.
Gesehen am 25.05.2022